2020
DOI: 10.1177/1010539520968455
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Posttraumatic Stress Disorder and Depression in General Population in India During COVID-19 Pandemic Home Quarantine

Abstract: Introduction Restrictions on movement of people and decrease in face-to-face human interactions are known to influence the psychological profile of people. Hence, the study was planned to study the prevalence of post-traumatic stress disorder (PTSD) and depression in general population of India during COVID-19 (coronavirus disease-2019) pandemic home quarantine. Material and Methods A web-based survey was conducted using Google Forms during April 2020 home quarantine. Questions on psychological impact (Impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 6 publications
0
32
3
Order By: Relevance
“…A study conducted during the first wave reported a comparatively lesser impact (33.2%) on the psychological health of the individuals (4). Another study reported that 28.2% of the participants showed PTSD-like symptoms [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted during the first wave reported a comparatively lesser impact (33.2%) on the psychological health of the individuals (4). Another study reported that 28.2% of the participants showed PTSD-like symptoms [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…51 Each item is rated on a fourpoint scale (based on severity) ranging from 0 for not at all to 3 for nearly every day. 50 In this study, the severity of depressive symptoms was grouped based on the overall scores ranging from 0 to 27 and classified as no/minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe depression (20)(21)(22)(23)(24)(25)(26)(27). The online version of the questionnaire is available here: https://patient.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
“…14 Several studies around the world reported a wide range of magnitude of depression among the public since the COVID-19 outbreak. The prevalence of depression among the general population was reported to be 20.1-48.3% in China, [15][16][17] 22.1% in the UK, 18 27.8% in the United States, 19 14.1% in India 20 and 67.1% in Egypt. 21 In a study done in Addis Ababa, Ethiopia, the prevalence of depression in an urban community was reported to be 12.4%.…”
Section: Introductionmentioning
confidence: 99%
“…2020;Saunders et al 2021;Serafini et al 2020;Vindegaard & Benroz 2020) and decrease in psychological well-being (Serafini et al 2020;Vindegaard & Benroz 2020) among the general population during COVID-19 pandemic. India witnessed a similar trend with significant deterioration in mental health (Rehman et al 2021;Singh & Khokhar 2021;Venugopal et al 2020) and well-being (Samal 2021;. Soon after the COVID-19 outbreak in India, a twenty percent rise in cases of mental illnesses became evident (Loiwal 2020).…”
Section: Introductionmentioning
confidence: 97%